The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1021/ie960392b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of C10−C14 Normal Alkanes in Near-Critical and Supercritical Regions:  Product Distributions and Reaction Mechanisms

Abstract: Thermal decomposition of C 10 -C 14 n-alkanes was studied under near-critical and supercritical conditions. The primary products were C 1 -C m-2 n-alkanes and C 2 -C m-1 1-alkenes, and the secondary products were cis-and trans-2-alkenes, n-C m-1 , n-C m+1 , and C m+2 -C 2m-2 normal and branched alkanes, where m is the number of carbon atoms in the reactant. The relative yields of the primary and secondary products were dependent upon the reaction conditions. Product distributions exhibited large pressure depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 38 publications
(72 reference statements)
12
112
0
Order By: Relevance
“…Song et al [10] investigated the condensed-phase pyrolysis of n-tetradecane at elevated pressures. Yu and Eser [11] studied the near-critical and super-critical phase thermal decomposition of C10-C14 normal alkanes at temperatures from 673 to 723 K and pressures from 1 to 10 MPa (initial pressure). Recently, Yuan et al [12] do an experimental and theoretical study of n-Heptane pyrolysis, they detected the pyrolysis products by using synchrotron vacuum ultraviolet photoionization mass spectrometry (SVUV-PIMS).…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [10] investigated the condensed-phase pyrolysis of n-tetradecane at elevated pressures. Yu and Eser [11] studied the near-critical and super-critical phase thermal decomposition of C10-C14 normal alkanes at temperatures from 673 to 723 K and pressures from 1 to 10 MPa (initial pressure). Recently, Yuan et al [12] do an experimental and theoretical study of n-Heptane pyrolysis, they detected the pyrolysis products by using synchrotron vacuum ultraviolet photoionization mass spectrometry (SVUV-PIMS).…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al [5,6] have reported some results on the thermal degradation of pure n-dodecane and n-dodecane mixtures containing different hydrogen donors, obtained in static stainless steel microreactors under temperatures from 773 to 823 K and pressures from 6.9 to 10 bar. Yu and Eser [7,8] have studied the near critical and supercritical phase thermal decomposition of C 10 -C 14 normal alkanes, including n-dodecane, in a Pyrex glass sealed tube under temperature from 673 to 723 K and pressures from 12.6 to 72.4 bar (the critical pressure of n-dodecane is 18.1 bar). In order to study the thermal decomposition of n-dodecane at higher temperatures than the previous papers [4,8], the present paper presents measurements at 950, 1000 and 1050 K. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical fluids have unusual high solubilities and therefore possibly minimize deposition on fuel pipe walls [16]. In addition to the solubilization effect, the near-critical or supercritical environment may also promote unique reactions and affect product distributions [29][30][31].…”
Section: Effect Of Co 2 On Df Thermal Stabilitymentioning
confidence: 99%